The Comparison of Effects of Alendronate and Raloxifene Treatment in Postmenopausal Women with Osteoporosis - Original Investigation - Gülcan Gürer; Ömer Faruk Şendur; Cavidan Ay; Ayhan Erkek; Bengü Beydağ Odabaşı (Galenos Yayinevi, 2006)
This study was performed to assess and compare the effects of raloxifene and alendronate for the treatment of postmenopausal osteoporosis. Thirty-two women with postmenopausal osteoporosis (raloxifene group:16 patients, alendronate group: 16 patients) were enrolled in this study. Bone mineral density (BMD) was measured at the proximal femur and lumbar spine by using dual-photon absorptiometry. Patients were divided into two groups randomly. BMD was measured twice as before and one year after from the treatment. Significant improvement was found at the end the treatment in both groups at lomber spine BMD (alendronate group: p<0.001, raloxifene group: p<0.05). There was no significant difference in of these groups and between two groups in femur BMD results (p>0.05). (Osteoporoz Dünyasından 2006; 12 (1): 12-14)